Preliminary investigation on nutritional values of grapes from three grapevine varieties (Vitis vinifera L.) planted in Ninh Thuan province - Hoang Son Le; Le Thanh Nguyen-Kim; Le Thuy Truc (Ciência e Técnica Vitivinícola)
The study aimed to preliminarily evaluate the nutritional values of the grapes from three table grape varieties (Vitis vinifera L.) including green grape, ‘Cardinal’ grape, and ‘Mariaue Finger’ grape from Ninh Thuan province, Vietnam. The analyses were conducted as per standard test methods. There were generally significant differences in energy-yielding nutrients among the three studied samples. These grapes presented moderate concentrations of carbohydrates and proteins ranging from 10.08 ± 0.48 to 12.07 ± 0.28 mg/100 g and from 0.37 ± 0.05 to 0.42 ± 0.04 mg/100 g, respectively, but no lipids content. The analysis revealed the presence of vitamin C and five minerals including Na, K, Mg, Fe, and Ca. The contents of Na, K, and Fe in green grapes were significantly higher than those of the two others. The phytochemical screening indicated the presence of flavonoids, steroids, and saponins, but not alkaloids, tannins, and terpenoids. The phenolic content in the three grape varieties was quantified at a moderate level, but low flavonoid content was found. The same pattern was also observed in the antioxidant activity (DPPH IC50), positively correlating to phenolic and flavonoid compounds contents. These findings scientifically contribute to the food database system, particularly those related to the new variety- the ‘Mariaue Finger’ grape -, which can be exploited for diet planning.